ÇOCUĞUN YAŞ, CİNSİYET, BİLİŞSEL YETENEK VE ANAOKULUNA GİTMESİNİN ANNENİN EV KADINLIĞI TUTUMUNA ETKİSİ - KESKİN, Sabiha (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The influence on maternal housekeeping of age, gender, cognitive efficiency and playschool attendance of the child was investigated from a survey of mothers and their 90 preschoolers of high-middle-class whose mean age was 69.2 SD3,5 mo. and of whom 56 (62%) were boys and 34 (38%) were girls. The cognitive ability of the children was assessed with Stanford Binet-12- oral questions and “Draw me a child picture” Goodenough criteria. The Protective attitude showed a positive correlation both with a democratic and oppressive approach. Indeed, mothers of boys were more protective (-0.13 versus -6.06), democratic (0.18 versus -3.03), oppressive (1.79 versus -6.06), but at the same time repining more about spouse disharmony (0.25 versus -9.09). Moreover, mothers of home-staying children were more democratic (0.85 versus -2.33, p=0.03**, for boys; 0.11 versus -8.33, for girls) than those of playschool attendees. In fact, mothers of home-staying boys were less protective (-7.69 versus -0.14) but at the same time more repulsive to house-work (-7.69 versus 0.16). Spouse disharmony increased maternal protection for all children (0.465***), especially for girl attendees (0.556***). On the other hand, disharmonious mothers of home-staying boys showed a repulsion to house-work (0.270*) inversely correlated with age (-0.268*) or cognitive development (-0.272*) of the child. Results.- The results were conclusive that an increased maternal protection was operating for those off-spring who is of male gender, weak and away from immediate maternal protective reach. Indeed, maternal protection is believed to deserve to be differentiated with a term as such “maternal anxiety of loss” since it is seemingly operating to detect even subtle signals of threat to the well-being of the offspring.